METODE PEMBELAJARAN GURU DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN MATEMATIKA KELAS IV DI MADRASAH IBTIDAIYAH SWASTA AT-TAQWA SAMBAS TAHUN PELAJARAN 2022-2023 - Fibry Damayanti; Susilawati; Sera Yuliantini (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This article aims to describe and find out about: 1) describe and analyze teacher learning methods in improving students' understanding of mathematics subjects; 2) describe and analyze the application of teacher learning methods in improving students' understanding of mathematics subjects; 3) Describe the obstacles teachers face in improving students' understanding of mathematics subjects. This research uses a qualitative approach and the type of research used is descriptive. The data collection techniques used were interviews, observation and documentation. Then the data analysis techniques used in this research are data reduction, data display/data presentation, and drawing conclusions. Meanwhile, the technique for checking the validity of the researcher's data uses triangulation techniques and member checks. The results of this research show that: 1) To improve students' understanding of mathematics, teachers include: a) Lecture method, b) Discussion method, c) Expository method, d) Problem solving method; 2) The application of teacher methods in improving students' understanding of learning is by using methods in a teaching and learning process. In the teaching process, the teacher not only explains and conveys a number of lesson materials to students, but the teacher also provides stimulation and encouragement so that the learning process occurs in the students; 3) The obstacles experienced by teachers are lack of time and infrastructure as well as lack of attention of students to the teacher's explanation and lack of ability of students to apply mathematical formulas that have been explained by the teacher in the questions given because students still have difficulty in solving problems. using mathematical formulas.